Silencing MEG3 protects PC12 cells from hypoxic injury by targeting miR-21 - Dan Deng; Hui Liang (Artificial Cells, Nanomedicine, and Biotechnology)
Increasing number of literatures highlighted lncRNA maternally expressed gene 3 (MEG3) as an emerging target for hypoxic-ischaemic brain damage (HIBD). This study attempted to assess the role of MEG3 in a cell model of HIBD. Expression of MEG3 in PC12 cells was suppressed by siRNA-mediated transfection, after which the cells were subjected to hypoxia. Cell viability, apoptosis, migration and the expression of related proteins were assessed. Furthermore, the downstream gene of MEG3 and its downstream signalling pathways were explored. We found that, down-regulation of MEG3 prevented hypoxic injury in PC12 cells, as hypoxia induced viability loss, apoptosis and migration repression were attenuated by transfection with MEG3 siRNA. Meanwhile, MEG3 acted as a miR-21 sponge. The neuroprotective functions of MEG3 silence were flattened when miR-21 was suppressed. Moreover, the deactivation of PI3K/AKT pathway and the activation of NF-κB pathway induced by hypoxia were attenuated by MEG3 silence. As expected, the effects of MEG3 silence on these two signalling were via miR-21. In conclusion, the neuroprotective effects of MEG3 silence on PC12 cells injured by hypoxia were observed in this study. Mechanistically, the neuroprotective effects of MEG3 silence on PC12 cells were via sponging miR-21 and thus regulating PI3K/AKT and NF-κB pathways.HIGHLIGHTSMEG3 is highly expressed in PC12 cells following hypoxic injury;Silence of MEG3 prevents hypoxia-induced cell damage in PC12 cells;MEG3 acts as a miR-21 sponge;MEG3 sponges miR-21 to regulate PI3K/AKT and NF-κB pathways.